Camelid Single-Domain Antibodies As an Alternative to Overcome Challenges Related to the Prevention, Detection, and Control of Neglected Tropical Diseases - Fernandes, Carla F. C.; Pereira, Soraya dos S.; Luiz, Marcos B.; Zuliani, Juliana P.; Furtado, Gilvan P.; Stabeli, Rodrigo G. (Frontiers in Immunology, 2017)
Due mainly to properties such as high affinity and antigen specificity, antibodies have become important tools for biomedical research, diagnosis and treatment of several human diseases. When the objective is to administer them for therapy, strategies are used in order to reduce the heterologous protein immunogenicity and to improve pharmacokinetic and pharmacodynamic characteristics. Size minimization contributes to ameliorate these characteristics, while preserving the antigen-antibody interaction site. Since the discovery that camelids produce functional antibodies devoid of light chains, studies have proposed the use of single domains for biosensors, monitoring and treatment of tumors, therapies for inflammatory and neurodegenerative diseases, drug delivery or passive immunotherapy. Despite an expected increase in antibody and related products in the pharmaceutical market over the next years, few research initiatives are related to the development of alternatives for helping to manage Neglected Tropical Diseases (NTD). In this review, we summarize developments of camelid single domain antibodies (VHH) in the field of NTDs. Particular attention is given to VHH-derived products, i.e., VHHs fused to nanoparticles, constructed for the development of rapid diagnostic kits; fused to oligomeric matrix proteins for viral neutralization; and conjugated with proteins for the treatment of human parasites. Moreover, paratransgenesis technology using VHHs is an interesting approach to control parasite development in vectors. With enormous biotechnological versatility, facility and low cost for heterologous production, and greater ability to recognize different epitopes, VHHs have appeared as an opportunity to overcome challenges related to the prevention, detection and control of human diseases, especially Neglected Tropical Diseases.